Development and testing of a river basin management simulation game for integrated management of the Magdalena-Cauca river basin. (April 2017) - Craven, Joanne; Angarita, Hector; Corzo Perez, G.A.; Vasquez, Daniel
Abstract: Sustainable basin management is important for both people and ecosystems. Increasing science-policy and inter-sectoral dialogue is recommended as a means to balance competing demands and achieve this; however, this dialogue is not necessarily easy to achieve. Here, we present a serious game aimed at communicating the complex relationships present in river basins and enabling dialogue between policy-makers and scientists in the Magdalena-Cauca basin, Colombia. Players guide the development of a fictional river basin over 30 years and the impacts of their decisions are simulated using WEAP water resources modelling software. The game has been used in various contexts. Here, experiences with stakeholders at a national forum in Bogota and with water professionals in Bangkok are discussed. The experience shows that the game is attractive to stakeholders, stimulates dialogue and provides interesting insights into the way computer models and stakeholders mental models can interact with and enrich each other. Graphical abstract: Highlights: A serious game was developed based on water resources modelling software. The game was evaluated in sessions with stakeholders and modellers. It has been popular and successfully used in various contexts. In the game, both computer models and players' mental models play central roles.